INDIKASI PENGARUH KEBUDAYAAN PERSIA DI SULAWESI SELATAN: KAJIAN ARKEOLOGI ISLAM - Chalid AS (Balai Arkeologi Provinsi Sulawesi Selatan, 2018)
transformation of Islamic teachings is one part of the historical phase in South Sulawesi. With various lines of arrival and a series of processes of Islamic socialization, it has implications for the acculturation and assimilation of culture. Persia as one of the cultural bases that played a role in the Islamization the process helped influence and colour the culture of Islamic societies in South Sulawesi. Archaeologically, the indication is illustrated by observing the attributes of Persian culture that attached to several steps of the tomb, headstone, and flag buildings in South Sulawesi. The method used forms analysis to obtain attributes of attributes, then the historical analysis is used to measure aspects of the similarity of ideas contained in these relics. Archaeologically, the indications and effects (transformation) of Persian culture in South Sulawesi is illustrated in (1) the tradition of establishing vaulted tomb buildings in people who are considered to have an important role in the sociological and religious aspects, the use of attributes in the form of lion embodiments in gravestones flags to represent the values (attitudes) of heroes, brave men, warriors, warfare, the use of figurative decorations on tombs as an attempt to demonstrate sociological conditions and personal values as a past inspiration in relation to maintaining the collective memory of society from time to time future.Transformasi ajaran Islam adalah salah satu bagian dalam fase sejarah di Sulawesi Selatan. Dengan berbagai alur kedatangan dan rangkaian proses sosialisasi Islam, memberikan implikasi terjadinya akulturasi dan asimilasi budaya. Persia sebagai salah satu basis budaya yang berperan dalam proses Islamisasi, turut memberi pengaruh dan mewarnai kebudayaan masyarakat Islam di Sulawesi Selatan.Secara arkeologis indikasi tersebuttergambar dengan mengamamati atribut kebudayaan Persia yang melekat pada beberapa peniggalan bangunan makam, nisan, dan bendera yang ada di Sulawesi Selatan. Metode yang digunakan adalah analisis bentuk untuk memperoleh unsur kesamaan wujud atribut, kemudiandigunakan analisis historis dalam menakar aspek kesamaan gagasan yang terkandungpada peninggalan tersebut. Secara arkeologis, bentuk-bentuk indikasi dan pengaruh (tranformasi) budaya Persia di Sulawesi Selatan tergambar pada (1) tradisi mendirikan bangunan makam berkubah pada orang yang dianggap memiliki peranan penting pada aspek sosiologi dan keagamaan, adanya penggunaan atribut berupa penggunaan perwujudan singa pada nisan dan bendera untuk merepresentasikan nilai (sikap) kepahlawan, pemberani, laki-laki, prajurit, peperangan, penggunaan ragam hias figuratif pada makam sebagai upaya dalam mendemostrasikan kondisi-kondisi sosiologis dan nilai kepribadian sebagai suatu inspirasi masa lalu dalam hubungannya menjaga ingatan kolektif masyarakat dari masa ke masa.